Distribution of dental anomalies in panoramic radiography at RSGMP Universitas Airlangga - Wahyuni, Otty Ratna; Saputra, Deny; Savitri, Yunita; Mulyani, Sri Wigati Mardi; Nurrachman, Aga Satria; Asymal, Alhidayati; Fandani, Fany (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: This research was aimed to determine the distribution of dental anomaly cases on panoramic radiographs at Universitas Airlangga Dental Hospital (RSGMP). Materials and Methods: This research used a descriptive observational design with a total sampling technique from panoramic radiographic data at the Radiology Clinic of RSGMP Universitas Airlangga during 2018–2020, which had cases of dental anomalies. Results: The result showed 116 cases of dental anomalies, with more incidence in female (64%) than in male (36%). The most common dental anomaly category was the number of teeth anomalies (47.41%), followed by tooth size anomalies (29.31%), tooth shape anomalies (23.28%), and there were no cases of anomalies in tooth structure and position. The most common types of dental anomalies were microdontia (27.59%), missing teeth/agenesis (25%), supernumerary teeth (22.41%), dilaceration (16.38%), talon cusp (3.45%), taurodontism (2.59%), macrodontia (1.72%), gemination (0.86%). Conclusion: The most common cases of dental anomalies were based on their categories, namely anomalies in the number of teeth, followed by tooth size, and tooth shape.